PENINGKATAN PERTUMBUHAN DAN PRODUKSI JAGUNG MANIS (Zea mays saccharata Sturt) DENGAN HIJAUAN Mucuna bracteata DAN BOKASHI - Aripin, Selamat; Anom, Edison; Yoseva, Sri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This study was conducted for the purpose to know an increase in growth and the production of  sweet corn with   the provision of forage Mucuna   bracteata and bokashi. This study has been  carried out in the garden experiment agricultural faculty university of riau, district tampan city  of pekanbaru. This research was conducted  over four months  from  september 2014  - january  2015.  This  is  a research experiment using a random group factorials design consisting of two factors. First factor is the provision of forage Mucuna  bracteata, second factor is bokashi. Observed the parameters, the rate of growth of plants, titled the root of ratio, higher plants, long leaves, time appear the male flowers, time appear female flowers, the age of the harvest,  Without  the skin of the tunny per weight, the diameter of the tunny without the skin, without  the skin of the tunny long, the production of the tunny per plot. The best there was in treatment of dose 15/ ha ton of forage Mucuna  bracteata and bokashi a dose of 10 tons/ha where plants sweet corn tend to improve the result although not significantly. yield is at best treatment forage mucuna bracteata 15 tons and tons bokashi has  4,82 10 kg/plot or an equivalent 16.06 tonnes/ha.The interaction of forage mucuna bracteata and bokashi with no real influence on all the parameters of observation, but tend to increase growth and the yield of sweet corn plant.   Keywords: Mucuna bracteata; Bokashi;  Zea mays